Proceedings of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Confer 2021
DOI: 10.18653/v1/2021.acl-short.6
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and Surprisal Jointly Deliver the Punchline: Exploiting Incongruity-Based Features for Humor Recognition

Abstract: Humor recognition has been widely studied as a text classification problem using data-driven approaches. However, most existing work does not examine the actual joke mechanism to understand humor. We break down any joke into two distinct components: the set-up and the punchline, and further explore the special relationship between them. Inspired by the incongruity theory of humor, we model the setup as the part developing semantic uncertainty, and the punchline disrupting audience expectations. With increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…Weller and Seppi (2019) demonstrated that the BERT-based classifier achieves superior results in humor recognition task on several existing datasets, and also proposed a new dataset composed of humorous Reddit posts. There are studies leveraging the setup-punchline structure of jokes for humor detection task using BERT senetence embeddings (Annamoradnejad and Zoghi, 2020) or GPT-2 (Xie et al, 2021). Peyrard et al (2021) applied various models -three transformer models (BERT, distilBERT, and RoBERTa), fastText-based representation, GPT-2, and LSTM, -to a collection of aligned humorous/non-humorous sentence pairs.…”
Section: Related Workmentioning
confidence: 99%
“…Weller and Seppi (2019) demonstrated that the BERT-based classifier achieves superior results in humor recognition task on several existing datasets, and also proposed a new dataset composed of humorous Reddit posts. There are studies leveraging the setup-punchline structure of jokes for humor detection task using BERT senetence embeddings (Annamoradnejad and Zoghi, 2020) or GPT-2 (Xie et al, 2021). Peyrard et al (2021) applied various models -three transformer models (BERT, distilBERT, and RoBERTa), fastText-based representation, GPT-2, and LSTM, -to a collection of aligned humorous/non-humorous sentence pairs.…”
Section: Related Workmentioning
confidence: 99%